2017
DOI: 10.1177/1541204017735568
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Adolescent Delinquency in a High-Risk Sample

Abstract: Research shows that adverse events experienced during childhood (i.e., adverse childhood experiences [ACEs]) are problematic, but few studies have examined race differences in the prevalence and impact of ACEs on delinquency. This study investigated these relationships using prospective data from approximately 600 high-risk families in the Longitudinal Studies of Child Abuse and Neglect. Ten ACEs were measured, five types of child maltreatment and five types of household dysfunction. White youth experienced a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 87 publications
11
69
0
Order By: Relevance
“…The investigators discovered that 25% of their sample had experienced two or more types of ACEs. In concert with this study, Fagan and Novak (2018) revealed that the higher the number of ACEs high risk children experienced, the greater their likelihood of self-reported alcohol use, marijuana use, violence, and arrest.…”
Section: Impact Of Traumasupporting
confidence: 60%
See 1 more Smart Citation
“…The investigators discovered that 25% of their sample had experienced two or more types of ACEs. In concert with this study, Fagan and Novak (2018) revealed that the higher the number of ACEs high risk children experienced, the greater their likelihood of self-reported alcohol use, marijuana use, violence, and arrest.…”
Section: Impact Of Traumasupporting
confidence: 60%
“…Multiple traumatic stressors will change the course of the student's life and place them at higher risk for adolescent delinquency, health disparities, incarceration, and early death (Felitti et al, 1998;Fagan & Novak, 2018). Trauma responses are complex, and children exhibit a wide range of responses to trauma stressors they have experienced.…”
Section: Impact Of Traumamentioning
confidence: 99%
“…Though it has only been in the past few years criminologists have assessed the specific relationship between ACEs and crime, the most recent work has started to examine how the effects of ACEs on offending may differ not only by crime type but also by sex and race/ethnicity (DeLisi et al, 2017; Fagan & Novak, 2018). For example, DeLisi and his colleagues (2017) found ACEs tended to increase the likelihood of engaging in sexual offenses but had inconsistent effects with respect to homicide, particularly among racial/ethnic subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…ACEs significantly increased the likelihood of residential placement for Black and Hispanic males but had no effect on White males; while ACEs predicted residential placement for Black females but had no effect for White or Hispanic females (Zettler et al, 2018). In a longitudinal study of race differences in the prevalence and impact of ACEs on juvenile delinquency, Fagan and Novak (2018) found that the number of ACEs significantly increased the likelihood of alcohol use, marijuana use, and arrest at age 16 among Blacks but not Whites, though Whites had a higher ACE exposure than Black youth.…”
Section: Introductionmentioning
confidence: 99%
“…13 Violence exposure is associated with increased risk of mental health problems, risky health-related behaviors (e.g., alcohol abuse, sexual risk-taking), chronic disease (e.g., coronary heart disease, diabetes), delinquency, and premature mortality. 14,15 Evidence for causal relationships between early exposure to violence, especially child maltreatment, and health outcomes is emerging. 16,17 This literature suggests racial and ethnic disparities in violence may be linked to other prominent health disparities.…”
Section: Introductionmentioning
confidence: 99%